PRACTICE OF ENDODONTIC RE-TREATMENT IN FOUR CITIES OF PAKISTAN - Nagi, Sana Ehsen; Khan, Farhan Raza; Rahman, Munawar (Journal of Ayub Medical College Abbottabad, 2017)
Background: Root canal re-treatment is the procedure of choice when the primary root treatment fails but patient is inclined toward salvage of the tooth. The re-treatment is often a challenging procedure owing to lack to the predictability in the outcomes. Since, there is a no single way of planning and executing such procedure, a study was planned to assess the knowledge, attitude and practice regarding endodontic re-treatment among Pakistani dentists. The effect of clinical experience on the re-treatment planning was also determined. Methods: A survey was conducted by distributing a questionnaire among 240 dentists practicing in four major cities of Pakistan. Frequency distribution of the gender, experience, designation of the participants etc. was determined. A case scenario was also shared and responses upon decision making were noted. Chi square test was applied to see if re-treatment decision of experienced dentists (>5 years’ practice) was significantly different than less experienced dentists. Results: Out of 240 forms, 160 were received (response rate of 66.67%). The most commonly reported reason for endodontic re-treatment was under prepared/ under filled canals. Nearly 40% participants reported doing re-treatment with hand instruments only and 15% did not employ any solvent during re-treatment. There were no significant differences between the less experienced and the more experienced dentists on re-treatment decisions. Conclusions: Almost half of the dentists reported inappropriate decision making in re-treatment. This shows that in endodontic re-treatment practice in major cities of Pakistan falls short of internationally accepted standards. There is a significant difference in treatment planning done by more experienced dentists compared to ones with <5 years’ clinical experience. Keywords: Endodontics; Failed root canals: Re-treatment; Survey; Root canal